Dengue: Lessons of an Outbreak - Siddiqui, Oves (J Clin Diagn Res, 2016)
INTRODUCTION: Since 1967 there have been many outbreaks of dengue in Delhi. In the year 2015 Delhi has suffered it’s one of the worst dengue outbreaks, with more than 15000 dengue confirmed cases and the highest number of deaths (60) in recent years. AIM: To determine the status of Dengue cases as compared to previous six years, the ratio of primary and secondary dengue cases and to review the effectiveness of the one test strategy (either NS1 antigen or IgM antibody) for the confirmation of Dengue. MATERIALS AND METHODS: A cross-sectional study was performed in the year 2015. A total of 7177 serum samples were tested for the confirmation of suspected cases of dengue at our institute. We performed dengue NS1 antigen and dengue IgM antibody ELISA tests for the confirmation of dengue cases in acute and convalescent fever cases respectively. Hundred random samples negative for NS1 antigen were tested for IgM antibody and 100 random samples negative for IgM antibody were tested for NS1 antigen. For determination of ratio of primary and secondary dengue cases, IgG Avidity ELISA was performed on random 76 dengue positive samples. RESULTS: Out of 7177 samples tested, 2358 were positive either by NS1 antigen or for IgM antibody from January to December. Percentage positivity rates for IgM antibody detection and NS1 antigen detection tests were 24.8% (626) and 37.1% (1732) respectively. Out of 100 NS1 negative samples 8 were positive for IgM antibody and out of 100 IgM negative samples 6 were positive for NS1 antigen. Among the 76 samples tested for dengue IgG Avidity ELISA 52 (68.4%) were found to be of secondary dengue. CONCLUSION: Number of dengue cases is constantly rising in Delhi since 2011 and 2014. IgM antibody detection and NS1 antigen detection both the tests should be performed for each patient. Due to the increased prevalence of past infection of dengue, percentage of secondary dengue cases is also increasing in Delhi.